2019
DOI: 10.1177/1460458218824742
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing of lifestyle modification documentation

Abstract: Lifestyle modification, including diet, exercise, and tobacco cessation, is the first-line treatment of many disorders including hypertension, obesity, and diabetes. Lifestyle modification data are not easily retrieved or used in research due to their textual nature. This study addresses this knowledge gap using natural language processing to automatically identify lifestyle modification documentation from electronic health records. Electronic health record notes from hypertension patients were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“… 36 , 37 Our investigation found that diagnosis codes from ICD-9 and ICD-10 and concepts identified using cTAKES and UMLS, were extensively used as features for substance use, alcohol use, and smoking status. 17 , 26 , 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
“… 36 , 37 Our investigation found that diagnosis codes from ICD-9 and ICD-10 and concepts identified using cTAKES and UMLS, were extensively used as features for substance use, alcohol use, and smoking status. 17 , 26 , 38 , 39 …”
Section: Resultsmentioning
confidence: 99%
“…37 So, in addition to medication-based treatment, telemonitoring applications should also strive for a behavior-related risk factor reduction by, for example, motivating for increasing sport activities following the principles of gamification. 38,39 A lack of viable business models hampers successful integration of these innovative diabetes telemonitoring services in Austrian standard care. 10,11,15 Despite experiencing positive effects on health parameters in the course of a longer term pilot telemonitoring project, diabetes patients were not willing to pay for these services for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…[96]. cTAKES was used to identify subtypes of patients with opioid misuse [46] and lifestyle modification [62]. Shoenbill et al combine cTAKES with rules and regular expressions on selected EHRs to make previously unseen data on lifestyle modification documentation visible.…”
Section: Relations Between Sbdh and Health Outcomesmentioning
confidence: 99%